2013
DOI: 10.1186/1471-2431-13-106
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of receiving therapy among very low birth weight 2-year olds eligible for Part C early intervention in Wisconsin

Abstract: BackgroundThe Individuals with Disabilities Education Act (Part C) authorizes states to establish systems to provide early intervention services (e.g., therapy) for children at risk, with the incentive of federal financial support. This study examines family and neighborhood characteristics associated with currently utilizing physical, occupational, or speech therapy among very low birthweight (VLBW) 2-year-old children who meet Wisconsin eligibility requirements for early intervention services (EI) due to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
0
27
1
1
Order By: Relevance
“…This varies from previous reports of race and insurance type impacting access to early intervention and is an encouraging finding. 11,12 We found that children referred for diagnostic ASD evaluation were receiving a mixture of both federally funded programing and privately obtained therapies. Among our sample, almost 70% of children received services under the Individuals with Disabilities Education Act (Part C and Part B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This varies from previous reports of race and insurance type impacting access to early intervention and is an encouraging finding. 11,12 We found that children referred for diagnostic ASD evaluation were receiving a mixture of both federally funded programing and privately obtained therapies. Among our sample, almost 70% of children received services under the Individuals with Disabilities Education Act (Part C and Part B).…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, utilization of Part C services has also been reported as higher among children with Medicaid. 12 Despite such disparities, recent outcome reports have shown that 71% of all Part C Infant and Toddler Program participants less than 3 years of age have greater than expected growth in knowledge and skills, and 52% of these participants exit the early intervention program with development within age-appropriate limits. 13 In conjunction with these concerns about service acquisition, increasing recognition of ASD behaviors by families and primary pediatric health care providers has led to long wait lists at tertiary ASD diagnostic clinics, with families waiting as long as 6 to 12 months or more for an evaluation.…”
mentioning
confidence: 97%
“…However, vocabulary delays were not included as a predictor in the study's analyses. Recent analyses by McManus et al (2013) of a very low birth weight cohort similarly did not include vocabulary delays as a predictor. Morgan et al (2012) reported that 48-month-old children with greater receptive vocabulary knowledge were less likely to be identified as developmentally delayed or disabled, including being diagnosed for communication problems.…”
Section: Early Vocabulary Delays and Later Speech/language Service Usementioning
confidence: 99%
“…Barriers for accessing early therapy services include low income, low maternal education and single family households (McManus et al, 2013). Caucasian children are five times more likely to access early intervention services than African-American children (Feinberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Caucasian children are five times more likely to access early intervention services than African-American children (Feinberg et al, 2012). Some studies have shown that children with Medicaid are less likely to access early intervention and early therapy services (Barfield et al, 2008; Rosenberg et al, 2008); while other studies suggest that children with public insurance, or specifically Medicaid, are more likely to enroll in therapy services than children with private insurance (McManus et al, 2013; Shapiro-Mendoza et al, 2013). Low referral rates, lack of family follow through, and stigma associated with utilizing services are also suggested to be the factors influencing under-enrollment for services for extremely low birth weight children (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%